Developing form/function relations in narrative texts - Berman, Ruth A. (Lenguas Modernas, 2017)
The paper elaborates on a central theme of the Berman and Slobin (1994) crosslinguistic study of narrative development: children's developing ability to express form/function relations in extended discourse. Here, formrefers to linguistic devices including bound morphemes, words and other lexical expressions, and syntactic constructions and processes, while functionrefers to the meaning and role of such deüces in the course of narrative production. Focus is on three features of this analysis: (l) The claim that initially the relation between linguistic forms and the narrative functions which they perform is restricted in both directions (limited forms for a given function, and limited function for given forms), (2) the idea that linguistic forms may emerge very early in development, but they will have extended developmental histories, and (3) the fact that we at present lack clear a prioricharacterization of which forms will perform what functions in a particular narrative context. These ideas are examined for linguistic forms such as prepositional markers of predicate-nominal relations, the English morpheme -ing, the Hebrew connective meaning and, and subject elision in English, Hebrew, and Spanish, and for narrative functions such as perspective taking, object description, and reference.